Islam Moderat sebagai Retorika Populisme Aktor Politik: Semiotika Akun @CakIminNow - Sriharyani, Yuni (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2024)
This study examines the populist rhetoric of political actor, Muhaimin Iskandar, delivered on @CakIminNow during the 2024 Indonesian presidential election campaign, especially in the tweet dated October 1, 2023 regarding the Celebration of Pancasila Sanctity Day. This study uses a critical paradigm and Roland Barthes' semiotic analysis technique in analyzing nine units of analysis posted on @CakIminNow. The results of this study have revealed that the representation of moderate Islam has been utilized as a tool of populist rhetoric by Muhaimin Iskandar (Cak Imin) as one of the vice presidential candidates in the 2024 election. In addition, moderate Islam is not only seen as a system of beliefs and religious practices but also as a commodity in political marketing communication efforts by political actors. In short, this populist rhetoric functions as a strategy to strengthen the political image and garner voter support during Indonesia’s 2024 presidential election campaign.